SUSTAINABLE SUPPLY CHAIN MANAGEMENT AND ITS EFFECTS ON THE PERFORMANCE OF SUGAR SUB-SECTOR IN KENYA - Panya, K. O.; Ochiri, G.; Achuora, J.; Gakure, R. W. (The Strategic Journal of Business & Change Management, 2021)
The main objective of this study was to find out the effects of sustainable supply chain practices on the performance of sugar sub-sector in Kenya. Specifically the study identified the effect of Green manufacturing and Green Procurement to the performance sugar companies in Kenya. The study employed descriptive research design. The target population was 600 respondents comprising of the management of sugar companies in Kenya, sugarcane farmers and sugar importers and exporters. Stratified random sampling was used with sample size of 30% of the target population, which comprised of 180 respondents. The study collected data using questionnaires. The study adopted both qualitative and quantitative data analysis techniques. This study used SPSS Version 21 and Microsoft word tools to aid in data analysis. Regression analysis was used to establish the relationship between the variables. Data analysis was conducted using descriptive statistics and inferential statistics by use of hierarchical moderated multiple regression analysis. It was concluded that proper implementation of green supply chain management practices leads to better performance in sugar sub-sector in Kenya. The study recommended that manufacturing firms should implement environmentally sound practices in all phases of the supply chain, beginning with procurement of raw materials to manufacturing. The study findings were of essence to regulators to enhance the level of implementation of supply chain management practices through enforcement of stricter environmental regulations and rewarding firms that implement these practices. In conclusion the study findings provided future researchers with a useful conceptual and methodological reference to carry out studies in this area especially in emerging economies like Africa.
Keywords: Green Manufacturing; Green Procurement